The Influence of Judicial Delays on Enterprises’ Activity - Beatrice LEUSTEAN; Ana DEMSOREAN; Diana SCURTU (Communications of International Proceedings, 2020)
Judicial delays are a common fact that later years increased its influence on the market performance. This study focuses on the relationship between judicial delays and market leavers, on the relationship between the Judicial Effectiveness and the Corruption Perception Index. The global and regional data analysis revealed strong-holds among these events. Another study was applied on European Union countries, for being able to empirically test and reflect through a regional quantifiable frame Romanian’s entrepreneur perception about judicial terms delays over the losses and bankruptcy spectrum their company experience.
Keywords: Corruption; Bankruptcies; Judicial Effectiveness; Correlation; Regression